A focused review on the tribological behavior of C/SiC composites: Present status and future prospects. Issue 9 (August 2023) - Diao, Quanwei; Zou, Hongbo; Ren, Xinyu; Wang, Chunshen; Wang, Yang; Li, Hongyu; Sui, Tianyi; Lin, Bin; Yan, Shuai
Abstract: Silicon carbide-based ceramic matrix composites have received extensive attention in recent years. Many excellent reviews have reported on the tribological behavior of carbon fiber-reinforced carbon and silicon carbide dual matrix (C/C-SiC) composites. However, a systematic overview of the tribological properties of carbon fiber-reinforced silicon carbide (C/SiC) composites does not exist. This review focuses on C/SiC composites and summarizes the key factors, including internal factors (constituent content, graphitization process, material structure and fiber direction), and various test conditions (pressure and speed, dry and wet, temperature, and counterparts) that affect their tribological behavior. Their wear mechanisms under different conditions are elaborated. Finally, some potential future development directions for improving the performance of C/SiC composites are proposed to provide high-quality ceramic matrix composites for engineering applications. These directions include structural modification, matrix modification, coating technology, laser surface texturing, and material genome method. Graphical Abstract: ga1